Unveiling the imprinted dance: how parental genomes orchestrate seed development and hybrid success - Muthusamy, Muthusamy; Pandian, Subramani; Shin, Eun-Kyuong; An, Ho-Keun; Sohn, Soo-In (Frontiers in Plant Science, 2024)
Parental epigenetic asymmetries, which contribute to the monoallelic expression of genes known as imprints, play a critical role in seed development in flowering plants. Primarily, differential DNA methylation patterns and histone modifications on parental alleles form the molecular basis of gene imprinting. Plants predominantly exhibit this non-Mendelian inheritance phenomenon in the endosperm and the early embryo of developing seeds. Imprinting is crucial for regulating nutrient allocation, maintaining seed development, resolving parental conflict, and facilitating evolutionary adaptation. Disruptions in imprinted gene expression, mediated by epigenetic regulators and parental ploidy levels, can lead to endosperm-based hybridization barriers and hybrid dysfunction, ultimately reducing genetic diversity in plant populations. Conversely, imprinting helps maintain genetic stability within plant populations. Imprinted genes likely influence seed development in various ways, including ensuring proper endosperm development, influencing seed dormancy, and regulating seed size. However, the functions of most imprinted genes, the evolutionary significance of imprinting, and the long-term consequences of imprinting disruptions on plant development and adaptation need further exploration. Thus, it is clear that research on imprinting has immense potential for improving our understanding of plant development and ultimately enhancing key agronomic traits. This review decodes the possible genetic and epigenetic regulatory factors underpinning genomic imprinting and their positive and negative consequences on seed development. This study also forecasts the potential implications of exploiting gene imprinting for crop improvement programs.